Artistic Research - Balkema, Anette W.; Slager, Henk (New York Rodopi, 2004)
Currently, advanced art education is in the process of developing (doctorate or PhD) research programs throughout Europe. Therefore, it seems to us urgent to explore what the term research actually means in the topical practice of art. After all, research as such is often understood as a method stemming from the alpha, beta or gamma sciences directed towards knowledge production and the development of a certain scientific domain. How is artistic research connected with those types of scientific research, taking into account that the artistic domain so far has tended to continually exceed the parameters of knowledge management? One could claim that the artistic field comprises the hermeneutic question of the humanities, the experimental method of the sciences, and the societal commitment of the social sciences. Will that knowledge influence the domain, the methodology, and the outcome of artistic research? Another major topic concerns not only the specificity of the object of knowledge of artistic research but above all whether and how artistic research and its institutional programs will influence topical visual art, its artworks and its exhibitions. These complex problematics with their various points of view and management models are mapped out through the contributions of theorists, curators, and institutions, from Belgium, France, Great-Britain, Italy, The Netherlands, Finland, Germany, and Sweden. May these contributions be a constructive impetus for a versatile debate which may influence the future role of advanced art institutions and the position of artistic research in the next decade.